2016
DOI: 10.1051/matecconf/20163802008
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of energy potential and power generation from tidal basin in coastal area of malaysia

Abstract: ! /),0 1 22+ '('(1 23+ '(2(-'. % '()2)2)45 1 *30 '3+5 '(2(-2. 1 3*3)657 '(2(-+. % 1-* 4. 6 8 6-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The tidal range found in Peninsular Malaysia is at Pelabuhan Klang with 3 m height which is passing the minimum requirement for tidal barrage implementation. While the Sabah and Sarawak have the highest tide range at Sejingkat with a tide height of more than 3 m. The data of the Malaysia Metrology Department from 2007 until 2011 indicate the highest tidal range of 5 m is found at Sabah and Sarawak [28]. Kuching Barrage located in Sarawak was built to mitigate flood in the city of Kuching has the potential for development into a tidal range power station as its highest tidal range of 6.8 m. The suitable tidal power plant scheme for Kuching Barrage (Figure 8) at Pending is operated using ebb generation during the barrage daily flushing operation.…”
Section: A Tidal Range Energymentioning
confidence: 95%
See 3 more Smart Citations
“…The tidal range found in Peninsular Malaysia is at Pelabuhan Klang with 3 m height which is passing the minimum requirement for tidal barrage implementation. While the Sabah and Sarawak have the highest tide range at Sejingkat with a tide height of more than 3 m. The data of the Malaysia Metrology Department from 2007 until 2011 indicate the highest tidal range of 5 m is found at Sabah and Sarawak [28]. Kuching Barrage located in Sarawak was built to mitigate flood in the city of Kuching has the potential for development into a tidal range power station as its highest tidal range of 6.8 m. The suitable tidal power plant scheme for Kuching Barrage (Figure 8) at Pending is operated using ebb generation during the barrage daily flushing operation.…”
Section: A Tidal Range Energymentioning
confidence: 95%
“…Both CO2 emissions and Malaysian population growth are proportionally and increase year by year. Electricity generation from burning fossil fuel will generate a huge volume of CO2 into the atmosphere and cause global warming [28], [29]. Global warming refers to increasing the average surface temperatures of the earth [30].…”
Section: National Renewable Energy Goalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other environmental issues such as effects on marine habitats, noise pollution, leakage, and magnetic field that may appear from TCT installation were discussed. In a study conducted by Yusoff et al, [58] to assess the tidal energy in Malaysia based on the analysis of the tides table in 2014, it was found that Klang Port has a good potential for harnessing tidal energy with an average tidal range between 0.4 m and 5.3 m. Nazri et al, [59] investigated sixteen locations across the Malaysian coastline to determine the potential of using the tidal range for power generation. Klang Port in Peninsular Malaysia meets the minimum height requirement (3m), while Sejingkat in Sabah and Sarawak exceeds this limit.…”
Section: Tidal Energy Resource In Malaysiamentioning
confidence: 99%